Burden of COVID-19 infection and lockdown measures on individuals with chronic diseases in Saudi Arabia: A national population-based study. Issue 12 (December 2022) - Al-Raddadi, Rajaa; Harakeh, Steve; Alamri, Turki; AlRaddadi, Zeyad; Alzahrani, Sami; Al-Rabia, Mohammed; Bakarman, Marwan
Abstract: Background: The recent COVID-19 crisis has placed a huge strain on the global health and economy. The toll of the damage on the human society exceeds the morbidity and mortality of the pandemic and the associated burden, considering the multidimensional impact on all aspects of life. Objectives: The present study assessed the specific impact of COVID-19 on individuals with chronic diseases including the Years Lost for Disability (YLD) burden of COVID-19 infection, and multidimensional impact on the disease management, adaptive lifestyle, and socioeconomic dimensions. Method: A national, population-based cross-sectional study was conducted among adult Saudi population. An internet-based questionnaire was used to collect sociodemographic characteristics, medical history, impact of COVID-19 lockdown on the management of the chronic disease, adaptive lifestyle, and impact of COVID-19 on family members. Additionally, data regarding eventual COVID-19 infection, severity and management were collected. YLD was estimated and normalized per 100, 000 persons. Result: Having a chronic disease was not associated with a greater risk of COVID-19 (relative risk [RR]=0.83, p = 0.153); however, it was associated with higher risk of declined physical activity (RR=1.30, p < 0.0001), deteriorated eating habit (RR=1.20, p = 0.002), sleep quality (RR=1.25, p < 0.0001), and overall health perception (RR=1.61, p < 0.0001), loss of family members due to COVID-19 (RR=1.96, p = 0.0001), and impacted household income (RR=1.11, p = 0.010). In case of COVID-19 infection, having a chronic disease was associated with increased risk of hospitalization (RR=5.04, p = 0.005) and having a moderate-to-severe form of COVID-19 (RR=6.00, p = 0.013). The overall YLD was estimated to be 17.7 per 100, 000 individuals, and there was no significant difference between individuals with chronic diseases and those without. Conclusion: COVID-19 entailed a substantial burden on the Saudi society in 2020, and individuals with preexisting chronic diseases suffered more important multidimensional impact, which need further research to assess the real impact of the pandemic and draw the pertinent lessons from the experience for future possible epidemics.